Speaking with confidence - Gold, Nick (UK: penguin business, 2020)
"This book shows readers why it's important to speak well and learn to communicate with others effectively. The text discusses the different types of people we talk with, but also related issues, including body language, bullying, interviews, dating, and much more"--
Includes index.
Morsheda Aktar
Keywords: Social skills; Interpersonal relations; Communication